Orthopädische Probleme bei älteren Marathonläufern - Steinacker, T.; Steuer, M.; Höltke, V. (Sportverletzung Sportschaden, 2001)
58 marathon runners with an age average of 44,5 years were examined 6 months before the marathon in Berlin orthopedically.The orthopedic examination shows spinal column faulty burdens, muscular dysbalances as well as overload damages in the area of the knee joints and the achilles tendons. 42 probationers began after a biannual training with the marathon, one had to give up. Occurred during the marathon-training with 27 of the probationers orthopedic problems, especially in the area of the knee joint and the area of the achilles tendon. During the marathon 18 of the partipicants finished with orthopädic troubles.The examination shows, which orthopedic troubles with older marathon runners appears. Beside a sport medical suitability examination, a premature aimed therapy is necessary with the appearance of troubles since normally chronic overload damages and joint-wear threaten. When keeping the corresponding handicaps, a long-time marathon-training is possible also in the higher age without health risks for overuse injuries.